Loss of phosphatase and tensin homolog (PTEN) increases Lysyl oxidase-like 2 (LOXL2) expression enhancing the growth of fallopian tube epithelial cells as three-dimensional spheroids - Angela Russo; Junlone Moy; Manead Khin; Timothy R. Dorsey; Alfredo Lopez Carrero; Joanna E. Burdette (Cancer Pathogenesis and Therapy)
Background: High-grade serous ovarian cancer (HGSOC) accounts for 70–80% of all ovarian cancer-related deaths. Multiple studies have suggested that the fallopian tube epithelium (FTE) serves as the cell of origin of HGSOC. Phosphatase and tensin homolog (PTEN) is a tumor suppressor and its loss is sufficient to induce numerous tumorigenic changes in FTE, including increased migration, formation of multicellular tumor spheroids (MTSs), and ovarian colonization. In murine oviductal epithelial (MOE) cells (the equivalent of human FTE) loss of PTEN results in the upregulation of transcripts associated with the extracellular matrix, with a specific focus on the elevation of lysyl oxidase-like 2 (LOXL2). Although LOXL2 is known to drive transformation and invasion in solid tumors and is associated with a poor prognosis in ovarian cancer, its specific role in the tumorigenesis of ovarian cancer originating from FTE remains unclear. Therefore, we aim to investigate whether LOXL2 mediates tumorigenesis from the fallopian tube epithelium. Methods: In this study, we utilized clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein 9 (CAS9) technology to delete LOXL2 in PTEN-deficient MOE cells to understand its role in mediating the oncogenic effects of PTEN loss. In addition, CRISPR-CAS9 was used to delete LOXL2 in OVCAR8 ovarian cancer cells. We monitored the changes in tumorigenic properties, such as migration, invasion, and growth of three-dimensional (3D) spheroids, to assess whether the loss of LOXL2 resulted in any changes. Results: We found that a reduction in LOXL2 expression did not significantly change the migration or invasive capabilities of PTEN-depleted MOE or human ovarian cancer cells. However, we found that a reduction in LOXL2 expression resulted in a significant reduction in 3D MTS formation and survival in both lines. Conclusions: These results reveal for the first time that PTEN loss in FTE cells increases LOXL2 expression through downregulation of Pax2, and LOXL2 deletion blocks 3D spheroid formation.